Heated Wood-Based Ethylene Scavenger for Active Packaging to Prevent Browning of Lentinula edodes - Si Young Ha; Hyeon Cheol Kim; Woo Soak Lim; Jae-Kyung Yang (BioResources)
Most mushrooms are sensitive to ethylene, and exposure leads to degradation in mushroom quality, particularly in appearance and organoleptic properties. This study investigated the feasibility of using heated wood for ethylene removal. The hypothesis was that ethylene accumulation can be limited by using heated wood-based ethylene scavengers in mushroom packaging. The applicability and benefits of heated wood-based ethylene scavengers in mushroom home delivery are discussed. The heated wood-based ethylene remover used in the courier maintained the color of Lentinula edodes during transportation. These results were supported by quantitative analysis, in which the ethylene concentration in packaging headspace was significantly reduced (p < 0.05) by the wood-based scavenger, and rate of weight change also showed significant improvement (p < 0.05) compared to the control. Overall, this heated wood-based ethylene scavenger has potential in terms of mushroom packaging and food shelf-life extension.